Gaya Hidup Sehat Lansia Yang Mempunyai Kadar Asam Urat Lebih Dari Normal Di Posyandu Lansia Turi 01 UPTD Puskesmas Kecamatan Sukorejo - Sunarti, Sunarti (Jurnal Keperawatan Malang, 2020)
Introduction: Uric acid metabolism of purine is the result of the end of one who had been a component of nucleic acids that was found in the nucleus of a cell of the body. A healthy lifestyle for patients gout in need to avoid the excess levels of uric acid more than normal. Aim: A healthy lifestyle for patients gout in need to take does not happen excess uric acid levels more than normal aim of this case study to know a healthy lifestyle for the elderly who suffered uric acid levels more than normal at the Posyandu Elderly the Turi 01 UPTD Puskesmas Kecamatan Sukorejo Method: The methodology it uses descriptive a case study ( case study ). Participants needed is 5 participants seniors levels have uric acid more than normal. Data collection was carried out by means of interview in accordance with a sheet interview guidelines. Result : The research results show that lifestyle elderly that experienced levels uric acid more than normal those in the are caused by diet less well as remain to consumed food that may lead to elevated levels of uric acid and the quality of sleep less. Conclusion: Based on this research in expect participants more monitor especially pattern menu balanced and deepening the information about a healthy lifestyle elderly who have levels urid acid more than normal.